A Novel LQI-Based Speed Control of Switched Reluctance Motors for High Performance Applications - Paulo M. Robson Costa; Marcelo Vinicius De Paula; Pedro J. Dos Santos Neto; Tarcio Andre Dos Santos Barros (IEEE Access, 2025)
The increasing use of Switched Reluctance Machines (SRMs) across various applications has been driven by their notable advantages and advancements in power electronics. However, controlling SRMs remains inherently complex due to their nonlinear characteristics and parameter variations at different operating points. To address this challenge, this paper proposes the implementation of a Linear-Quadratic-Integral Regulator (LQI) for precise speed control of SRMs. The LQI controller, renowned for its optimal control capabilities, offers several benefits, such as favorable dynamic response, and robustness against disturbances and changing parameters. Unlike traditional controllers, the absence of an inner current control loop results in reduced torque ripple at the phase commutation frequency, simplifying design and implementation. By using PWM for voltage command, torque ripple at the switching frequency is reduced, and noise due to magnetostriction is minimized. A comprehensive design procedure for the proposed LQI speed control scheme is outlined, followed by a comparative analysis with established SRM controllers based on Proportional-Integral (PI) and Hysteresis (HC) controllers. Experimental validation of the proposed controller is provided, illustrating its superior performance across various operating points. The results demonstrate improved dynamic response, enhanced disturbance robustness, reduced torque ripple, a superior switching frequency spectrum, and minimal computational burden for embedded implementation.